Impact of energy certification on GHG Emissions - Lee, Jia Ying (Nanyang Technological University, 2019)
Energy benchmarking and certification programs are promising in identifying buildings with lower carbon footprint of greenhouse gas emission. It is necessary to examine and measure the reduction in greenhouse gas emissions for green certified building compared to non-certified buildings to ascertain the impact of certifications. This research documents both the impact of energy certification, and other property features and energy usage patterns on greenhouse gas emissions. A linear regression model for greenhouse gas emissions intensity is developed for the City of Seattle based on numerous explanatory variables like; location; property age, area and usage; and energy use types and intensity. Results from the Wilcoxon rank sum test indicates that greenhouse gas emissions for energy certified buildings is lower than non-certified buildings. Other important explanatory variables are also discussed and can be considered for further investigations.